A Debate on the Proposition that Self-report is the Gold Standard in Assessment of Pediatric Pain Intensity. Issue 8 (August 2015) - Twycross, Alison; Voepel-Lewis, Terri; Vincent, Catherine; Franck, Linda S.; von Baeyer, Carl L.
Abstract : Objectives and Methods: Self-report is often represented as "the gold standard" in assessment of pain intensity in children. We evaluate arguments for and against this claim and consider its implications for pain management. Results: Those in the support of the proposition argue that, when children are able to self-report, treatment decisions should be made based on these scores in line with current evidence-based recommendations. Pain is a subjective phenomenon and can be assessed only via self-report. Treating self-report scores as the gold standard is the only valid way for health care professionals to decide on appropriate treatment. Those against the proposition contend that reliance on self-reported pain scores for analgesic treatment decisions is inappropriate as they oversimplify the pain experience, yield only marginal information on which to base treatment decisions, and potentially place children at significant risk for adverse events. Self-reports of pain intensity sometimes contradict well-founded estimates based on other evidence. Wide variation between children in the meaning of pain scores precludes easy interpretation. Discussion: We conclude that self-report, when available, can be considered a primary source of evidence about pain intensity. However, it cannot be treated as an unquestioned gold standard. Instead, hierarchical or bundled approaches should be used, taking into account self-report as well as the many individual and contextual factors that influence pain including clinical history, patient preferences, and response to previous treatments. Alternate models are presented to guide further practice and research.